The non-linear optical and gas sensing properties of ultra-thin films - Roberts, M. P. S. (Cranfield University, 1997)
It is not often that a single experiment opens up a new direction of research. In this report, the optical properties of a series of organic molecules, of the form 2,4-bis((N-methyl-N-alkylamino)phenyl)squarine, which are symmetrical about their centre point, are investigated. By conventional thinking, these molecules should not show any even order non-linear optical effects; the generation of second, fourth or sixth harmonics of the incident light. In fact, significant second harmonics are generated by the materials, x(2)=25-pm v-1. This fact in itself is noteworthy, but the additional fact that the efficiency of the conversion is over two times greater than any other previously reported material is exceptional. The door is now open to an entirely new class of non-linear optical materials. In this report a thorough characterisation of the organic molecules is made by a variety of techniques; polarised second harmonic generation, quartz crystal micro balance and grazing angle X-ray diffraction. A mechanism for this new phenomenon, based on intermolecular charge transfer is developed. In a world of ever tightening pollution control legislation the need for sensors which can accurately measure the concentrations of various pollutant gases is becoming more important. In this report the pollutant sensing properties of a series of organic molecules, 2,4-bis((N-methyl-N-alkylamino)phenyl)squarine, are investigated. The series of compounds was found to be sensitive to nitrogen dioxide in concentrations of as little as 1 part per million in air, but the changes produced in the molecules were non-reversible. It is very rare to accidentally stumble across a molecule with ideal properties. A molecule must usually be modified to achieve optimum properties. In this report the steps taken in the molecular engineering of a new selective and reversible gas sending molecule are also reported. 1-(4-hydroxyphenyl)-2-(1-octadecyl-4-quinolinium iodide) ethene shows sensitivity to ammonia gas in concentrations as low as 25 parts per million in air. The response is fully reversible and can be detected using a surface plasmon resonance based sensor. In the search for new technical solutions to old problems simple solutions are often overlooked. The final section off this report describes a simple gas sensing technique, which had been available in many research institutions, but overlooked in favour of more complex solutions.